2019
DOI: 10.1016/j.jhep.2018.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the crosstalk between cytokine-induced killer cells and myeloid-derived suppressor cells in hepatocellular carcinoma

Abstract: Background: Cytokine-induced killer (CIK) cell-based immunotherapy is effective as adjuvant therapy in early stage hepatocellular carcinoma (HCC) but lacks efficacy in advanced HCC. We investigated immune suppressor mechanisms focuing on CIKs and myeloid-derived suppressor cells (MDSCs).Methods: MDSCs were quantified by flow cytometry and quantitative real-time PCR. Cytokines were detected by cytokine array. An LDH cytotoxicity assay was performed in the presence or absence of MDSCs to study CIK function again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 45 publications
2
93
0
Order By: Relevance
“…37 In addition, we have demonstrated that adoptive cell transfer of CIK cells into tumor bearing mice induced inflammatory mediators (e.g., CX3CL1, IL-13) in the TME and an increase of tumor infiltrating MDSCs leading to impaired anti-tumor activity in two different murine HCC tumor models. 38 MDSCs efficiently suppressed the cytotoxic activity of CIK cells in vitro. Tadalafil treatment, a phosphodiesterase-5 (PDE5) inhibitor, has previously been shown to reverse MDSC suppressor function via ARG1 and iNOS blockade.…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 92%
See 1 more Smart Citation
“…37 In addition, we have demonstrated that adoptive cell transfer of CIK cells into tumor bearing mice induced inflammatory mediators (e.g., CX3CL1, IL-13) in the TME and an increase of tumor infiltrating MDSCs leading to impaired anti-tumor activity in two different murine HCC tumor models. 38 MDSCs efficiently suppressed the cytotoxic activity of CIK cells in vitro. Tadalafil treatment, a phosphodiesterase-5 (PDE5) inhibitor, has previously been shown to reverse MDSC suppressor function via ARG1 and iNOS blockade.…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 92%
“…Treatment of MDSCs with a PDE5 inhibitor suppressed MDSCs suppressor function and enhanced CIK activity against human HCC cell lines in vitro. 38…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…Other strategies targeting immunosuppressive cells have been tested in the preclinical setting. The FDA-approved MDSCs inhibitor Tadalafil may enhance the Cytokine-induced killer (CIK) cell-based immunotherapy in HCC patients [138].…”
Section: Preclinical Studies In Hcc Immunotherapymentioning
confidence: 99%
“…The application of PDE5 inhibitors, including sildenafil, tadalafil, and vardenafil, can reduce the production of ARG1 and iNOS in MDSCs, abolish the inhibitory activity of MDSCs, reduce the number of T regs , and thus greatly delay the progression of tumors [87][88][89][90]. Treatment with tadalafil combined with cytokine-induced killer (CIK) cell-based immunotherapy enhanced CIK activity against human hepatocellular carcinoma (HCC) cell lines in vitro [91]. Nitroaspirin is another inhibitor of ARG1 and iNOS that reduces ROS generation [92].…”
Section: Inhibition Of Immunosuppressive Functionsmentioning
confidence: 99%